Pesticide Regime Can Negate the Positive Influence of Native Vegetation Donor Habitat on Natural Enemy Abundance in Adjacent Crop Fields - Pandey, Sunita; Johnson, Anne C.; Xie, Gang; Gurr, Geoff M. (Frontiers in Ecology and Evolution, 2022)
The benefits of non-crop vegetation to conservation biological in adjacent crops have often been demonstrated. Other studies have established that pesticide use can negatively impact natural enemies; but little is known about the outcomes from providing non-crop vegetation in systems with pesticide use. Here we conducted a natural experiment, sampling arthropods from within a set of four fields with varying pesticide use intensities that were otherwise similar and had perennial native vegetation adjacent to a single edge. Bayesian network analysis was applied to model the entire data set, then sensitivity analysis of numbers of arthropods captured in pitfall traps and sticky traps revealed that the overall effect of pesticide toxicity was large. Numbers of multiple arthropod taxa were especially strongly reduced in fields with pesticide regimes that had greater calculated toxicity scores. The effects on natural enemy numbers of the presence of adjacent perennial native vegetation was weaker than the effect of pesticide regime for all taxa except for Staphilinidae, for which it was equivalent. The benefit to in-crop numbers of natural enemies from the adjacent vegetation was strongest for ground active Araneae, Formicidae, and Dermaptera. Descriptive statistical analysis of the spatial distribution in the least heavily sprayed field suggested that the native vegetation was donor habitat for in-crop natural enemies, especially Hymenoptera, Dermaptera, and Formicidae, with numbers elevated close to the native vegetation, an effect that was apparent for around 100m. Conservation of invertebrates in agricultural landscapes, including efforts to promote natural enemies for conservation biological control, are strongly impeded by ‘real world’ pesticide regimes that include frequent applications and toxic compounds. Landscape features such as perennial native woody vegetation are potentially important refuges for a wide range of natural enemy taxa. The donor habitat effect of such refuges can elevate in-crop densities of these important ecosystem service providers over a scale of around 100 m, implying scope to enhance the strength of biological control in large fields (around 4 ha) by use of entirely wooded margins provided pesticide use is moderated.